Social dialogue and reorganization of labor and power relations nowadays / Diálogo social e reordenamento das relações de trabalho e de poder na atualidade - Figueiredo, Bruno de Oliveira; Souza, José dos Santos (Sociedade em Debate, 2020)
The article discusses the meaning and development of social dialogue in the current stage of capital development. Its purpose is to explain the political and ideological character of social dialogue in the context of the relationship between social classes. The analysis shows the constitution of an institutional engineering in the scope of the State that seeks to guarantee in a renewed way the harmonization of interests of entrepreneurs, workers and the State, based on the perspective of social dialogue. As a conclusion, the article points to evidence that social dialogue currently, under the pretext of renewing the relations between capital and labor, is nothing more than a strategy of renewal of the mechanisms of mediation of the class conflict to guarantee the maintenance of bourgeois hegemony in a context of organic crisis of capital. O artigo discute o significado e o desenvolvimento do diálogo social no estágio atual de desenvolvimento do capital. Seu objetivo é explicar o caráter político e ideológico do diálogo social no contexto da relação entre as classes sociais. A análise evidencia a constituição de uma engenharia institucional no âmbito do Estado que visa garantir de forma renovada a harmonização de interesses de empresários, trabalhadores e Estado, com base na perspectiva da concertação social. À título de conclusão, o artigo aponta evidências de que o diálogo social, na atualidade, à pretexto de renovar as relações entre capital e trabalho, nada mais é do que uma estratégia de renovação dos mecanismos de mediação do conflito de classes para garantir a manutenção da hegemonia burguesa em um contexto de crise orgânica do capital